Strengthening Destination Branding Through Local Product Innovation in Watusigar Village, Ngawen, Gunungkidul - Wiyatiningsih Wiyatiningsih; Tutun Seliari; Cheryl Marlitta Stefia; Maria Kinanthi Sakti Ning Hapsari; Angelica Riwu Kore (Faculty of Smart Technology and Engineering, Universitas Kristen Maranatha, Bandung, Indonesia, 2023)
Kalurahan Watusigar, which declared itself a conservation village, has a strategic location as the main access point for tourists from the north and east to the tourism area in Gunungkidul Regency, offering the opportunity to pioneer a green tourism village. The local community of Kalurahan Watusigar has initiated various initiatives through collaboration with relevant stakeholders. One such collaboration, with the Research and Community Service Institution of Duta Wacana Christian University (LPPM UKDW), is a community service activity aimed at strengthening destination branding through training for local product innovations of eco prints. The selection of eco print products is based on the availability of plants in the Watusigar area that can be used as natural dyes. The objective of this community service activity is to focus on developing the branding of Kalurahan Watusigar as a conservation village and green tourism village through local product innovation using natural materials and marketing strategies in accordance with digital technology. The target audience for this activity is the community members and Karang Taruna members of Kalurahan Watusigar. This community service activity introduces the eco print product ecosystem, which is the value chain of eco print products starting from creation, production, distribution, consumption, and conservation, utilizing action research methods through training, discussions, and workshops. The result of this community service activity is the expansion of knowledge about plants and materials in the environment to be used as environmentally friendly craft products. The eco print product innovation is an essential step in creating a creative economy ecosystem in Kalurahan Watusigar.